Institutionalising emergent organisation in health and social care. Issue 7 (17th July 2019) - Allen, D.
Abstract : Purpose: The purpose of this paper is to argue for the institutionalisation of emergent forms of organisation in health and social care and offer a conceptual framework for this purpose. Design/methodology/approach: Drawing on ethnographic research on the organising work of nurses and Translational Mobilisation Theory, this paper extends two classic Straussian sociological concepts – illness trajectory and articulation work – to conceptualise emergent organisation as Care Trajectory Management. Findings: Failures of coordination are well-recognised threats to quality and safety and recent decades have witnessed an explosion of neoliberal technologies and governance arrangements designed to "measure and manage" these risks. Yet in a significant and growing proportion of health and social care provision successful service integration depends not on rational planning, but iterative negotiations and adjustments in response to contingencies. While ubiquitous in health and social care systems, these emergent forms of organisation lack legitimacy, the work involved is relatively invisible and practice is poorly served by prevailing management discourses. Originality/value: The Care Trajectory Management Framework provides an alternative discourse and logic on which to develop strategies and technologies to support emergent organisational processes in acute and community care contexts.